Same-sex partners the social demography of sexual orientation - Baumle, Amanda K.; Compton, D'Lane R. (D'Lane Rebecca), 1977-; Poston, Dudley L., 1940- (Albany : SUNY Press, 2009)
A demographic portrait of gay and lesbian couples who live together in committed relationships.
Same-sex partnering data in the 2000 U.S. census : an overview -- Patterns of same-sex partnering in metropolitan and nonmetropolitan America -- The residential segregation of gay males and lesbians from heterosexuals -- Gay male and lesbian enclaves in the San Francisco Bay area -- Factors affecting the migration decision of gay men and lesbians -- Characteristics of same-sex families -- The effects of sexual orientation on dimensions of family attachment -- The economic cost of homosexuality -- Sexual orientation and occupational segregation.
Bibliographic Level Mode of Issuance: Monograph
English
Includes bibliographical references (p. 197-209) and index.
Keywords: Gay men -- United States -- Statistics; Gay couples -- United States -- Statistics; Lesbians -- United States -- Statistics; Lesbian couples -- United States -- Statistics